2012
DOI: 10.1111/j.1533-2500.2012.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

mild Procedure for Lumbar Decompression: A Review

Abstract: Lumbar spinal stenosis (LSS) is characterized by narrowing of the spinal canal with impingement of the spinal cord by surrounding tissues of bones. Current management options for LSS include rest, medications, physical therapy, epidural steroid injections, alternative medicine, and surgical decompression. Because each modality of treatment has its own set of limitations, there is a need for a safe, effective, and cost-saving treatment for LSS. mild is a minimally invasive procedure for treatment of degenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…There is known potential for significant morbidity and mortality associated with LL. [1][2][3] Current literature suggests that placement of an interspinous spacer (ISS) is a less invasive and potentially equally effective treatment option when compared to LL [4][5][6][7] ; however, systematic reviews of primary research have demonstrated that use of ISS devices is associated with higher costs and reoperation rates. [8][9][10] Still, the causes of the higher reoperation rate were not identified.…”
Section: Introductionmentioning
confidence: 99%
“…There is known potential for significant morbidity and mortality associated with LL. [1][2][3] Current literature suggests that placement of an interspinous spacer (ISS) is a less invasive and potentially equally effective treatment option when compared to LL [4][5][6][7] ; however, systematic reviews of primary research have demonstrated that use of ISS devices is associated with higher costs and reoperation rates. [8][9][10] Still, the causes of the higher reoperation rate were not identified.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on MILD is still maturing, as most of the published studies are case series not randomized controlled trials . However, these studies have shown great benefit in improving patient symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…MILD was met with both optimism and skepticism. Many case reports and retrospective observational studies supported MILD's claims, but unfortunately, there has been a lack of evidence from prospective blinded trials . None of the current literature on MILD examined how it could affect health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…The standard methodology used to perform percutaneous lumbar decompression has been previously described .…”
Section: Methodsmentioning
confidence: 99%